Qualitatively Examining Self-Regulation and Affect of First-Year Writing Students - Payne, Erica Lee (2021)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Erica Lee Payne entitled, “Qualitatively Examining Self-Regulation and Affect of First-Year Writing Students”, submitted in May 2021. Thesis advisor is Dr. Tammy Gregersen and thesis co-advisor is Dr. Rachel Buck. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).